2020
DOI: 10.1155/2020/8842206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Failure Characteristics and Strength Criterion of Coal‐Rock Combined Body with Different Height Ratios

Abstract: In underground mining and roadway support engineering of coal mine, the coal and rock layers bear loads together; therefore, the deformation and mechanical characteristics of the coal-rock combined bodies are not the same as those of the pure coal or rock bodies. In this paper, conventional triaxial compression tests of coal-rock combined bodies with different height ratios were conducted. And the stress and deformation characteristics of coal-rock combined body were studied and the experimental results were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…e coal samples were selected from the standard specimen made of coal blocks in a coal mine in Shanxi Province of China. e coal blocks obtained from the underground were processed into standard cylindrical coal samples with a diameter of 50 mm and a height of 100 mm by using drilling, cutting, and grinding [22][23][24]. e experimental coal samples are shown in Figure 2.…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…e coal samples were selected from the standard specimen made of coal blocks in a coal mine in Shanxi Province of China. e coal blocks obtained from the underground were processed into standard cylindrical coal samples with a diameter of 50 mm and a height of 100 mm by using drilling, cutting, and grinding [22][23][24]. e experimental coal samples are shown in Figure 2.…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…With increasing coal-rock ratio, the failure degree of the test piece gradually decreased, and the fracture form gradually changed from fragmentation to collapse. Wang et al [20] conducted conventional triaxial compression tests on coal-rock combinations with different high coal-rock ratios, studied the stress and deformation characteristics of coal-rock combinations, and analyzed the test results under different strength criteria. Huang and Liu [21] analyzed the influence of the loading and unloading rate and path on the mechanical properties of composites of coal and rock.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies carried out uniaxial compression tests on coal-rock combinations with different rock-coal height ratios to study the influence of rock-coal height ratio on the mechanical properties and progressive failure mechanism of coal-rock combinations. These studies found that the macroscopic failure initiation stress, peak stress, uniaxial compressive strength, and elastic modulus of coal-rock combinations appear as the rock-coal height ratio decreases [12][13][14][15]. Wu et al conducted an experimental analysis and theoretical verification of rock-coal-anchor (RCB) composite material systems from different angles, and found that the failure of rock-coal composite specimens was caused by tensile and shear cracks, and the reinforcement formed in the composite material system after anchoring limited the areas where cracks might appear in the specimens [16].…”
Section: Introductionmentioning
confidence: 99%